2019
DOI: 10.1037/tep0000234
|View full text |Cite
|
Sign up to set email alerts
|

Conquering the maternal wall: Trainee perspectives on supervisory behaviors that assist in managing the challenges of new parenthood during clinical internship.

Abstract: Women comprise three quarters of students who graduate from psychology doctoral programs (Cope, Michalski, & Folwer, 2016), but gender disparity in pay and position prestige persist in the workforce (American Psychological Association, 2018;Wicherski, Mulvey, Hart, & Kohout, 2011). Women who are mothers may experience a "maternal wall" (Crosby, Williams, & Biernat, 2004;Williams, 2005) that further impedes professional advancement. Because supervisors are positioned to facilitate trainees' professional develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…National and site-level policies must be reexamined and enforced across all training settings to ensure that marginalized trainees are supported. Additionally, peer support and mentorship opportunities should be made available to trainees (Grassetti et al, 2019). Lastly, academic advisors and directors of clinical training should be aware of possible identity-based harassment issues their students may face and create an environment where students can report harassment without repercussions.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…National and site-level policies must be reexamined and enforced across all training settings to ensure that marginalized trainees are supported. Additionally, peer support and mentorship opportunities should be made available to trainees (Grassetti et al, 2019). Lastly, academic advisors and directors of clinical training should be aware of possible identity-based harassment issues their students may face and create an environment where students can report harassment without repercussions.…”
Section: Recommendationsmentioning
confidence: 99%
“…Further actions that can be taken by supervisors to proactively deal with these problems and strengthen the supervisory relationship include those highlighted by Grassetti, Pereira, Hernandez, and Fritzges-White (2019). This article puts forward self-disclosure, flexibility, and corrective feedback as powerful tools to support marginalized trainees.…”
Section: Recommendationsmentioning
confidence: 99%
“…Similarly, McKinley (2019), Port (2019), and Qi, Wang, Wu, and Luo (2019) describe the important role supervisors play in helping international trainees acculturate to the country they are now working in by examining the sociocultural context of the client and the supervisee. Finally, the critical role supervisors play in making accommodations, for supervisees with physical disabilities (Pearlstein & Soyster, 2019) and new mothers (Grassetti, Pereira, Hernandez, & Fritzges-White, 2019), is explored, with a focus on elucidating the negative impacts (Output in Figure 1) of supervisors questioning their supervisee’s ability to meet the demands of graduate training.…”
Section: Narrative Inquires: How They Align With the Generic Model Of...mentioning
confidence: 99%
“…Many of the authors describe experiencing their supervisor(s) as having acted with prejudice and/or having microaggressed against them (Grassetti et al, 2019; Jendrusina & Martinez, 2019; McKinley, 2019; Patallo, 2019; Pearlstein & Soyster, 2019; Qi et al, 2019). Importantly, their experiences also revealed that supervisors who embraced cultural humility to explore the impact of supervisees’ intersectionality on their personal identity, professional identity (Thomas et al, 2019), and the power differentials within the supervisory triad (Blasini-Méndez, 2019; Hooley, 2019) facilitated more positive supervisee and clinical outcomes (Grassetti et al, 2019; Jendrusina & Martinez, 2019; McKinley, 2019; Patallo, 2019; Pearlstein & Soyster, 2019; Qi et al, 2019). Patallo (2019) provides illustrative examples and specific suggestions for supervisor development to incorporate cultural humility in supervisory relationships.…”
Section: Narrative Inquires: How They Align With the Generic Model Of...mentioning
confidence: 99%
“…Although the PPRP series was primarily focused on challenges experienced by practicing psychologists, two of the articles (i.e., DeMarce, 2007; Stratton et al, 2007) focus on the experiences of trainees. Similarly, a recent article in Training and Education in Professional Psychology highlights the unique supervisory experiences and challenges of new mothers during clinical internship (Grassetti et al, 2019). This interest in the challenges and life events experienced by graduate students was also the focus of an article in the American Psychological Association (APA) Monitor on Psychology that discussed how academic programs can provide support for graduate students when they experience significant life stressors.…”
mentioning
confidence: 99%